2014
DOI: 10.1136/gutjnl-2014-307348
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of small-bowel neoplasia in Lynch syndrome assessed by video capsule endoscopy

Abstract: NCT00898768.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
44
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 28 publications
2
44
1
Order By: Relevance
“…Retrospective analyses showed a median age at diagnosis of 39 (range 11 -81) years [3,5]. Recently, we showed that the prevalence of small bowel neoplasia (SBN) in asymptomatic LS patients as assessed by video capsule endoscopy (VCE) was markedly lower than previously estimated [6,7]. SBN was present in only 3 of the 200 patients (1.5 %) who underwent a VCE procedure (2 duodenal adenocarcinomas and 1 duodenal tubulovillous adenoma with low grade dysplasia) [6].…”
Section: Introductionmentioning
confidence: 98%
“…Retrospective analyses showed a median age at diagnosis of 39 (range 11 -81) years [3,5]. Recently, we showed that the prevalence of small bowel neoplasia (SBN) in asymptomatic LS patients as assessed by video capsule endoscopy (VCE) was markedly lower than previously estimated [6,7]. SBN was present in only 3 of the 200 patients (1.5 %) who underwent a VCE procedure (2 duodenal adenocarcinomas and 1 duodenal tubulovillous adenoma with low grade dysplasia) [6].…”
Section: Introductionmentioning
confidence: 98%
“…Although GISTs at the distal duodenum are less common than those at the D2, approximately 42.7% of these tumors are located in the D3 and D4 of the entire duodenum . The prevalence of small bowel neoplasia in asymptomatic patients with Lynch syndrome was found to be 1.5%, and all neoplastic lesions were located in the duodenum and could be reached by conventional gastroduodenoscopy . The duodenum is the most frequently involved segment with small bowel adenocarcinoma, accounting for approximately 55–82% of the cases .…”
Section: Introductionmentioning
confidence: 99%
“…6 The prevalence of small bowel neoplasia in asymptomatic patients with Lynch syndrome was found to be 1.5%, and all neoplastic lesions were located in the duodenum and could be reached by conventional gastroduodenoscopy. 10 The duodenum is the most frequently involved segment with small bowel adenocarcinoma, accounting for approximately 55-82% of the cases. 8 Furthermore, an increase in duodenal tumors has significantly contributed to the increasing incidence of small bowel adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…12 Surveillance using video capsule endoscopy has detected duodenal adenocarcinoma and adenomatous polyps in asymptomatic patients, which could be managed with solely upper endoscopy techniques. 13 Peutz-Jeghers' syndrome (PJS) also has elevated risk of gastrointestinal cancers that arise from adenomas and hamartomas, with relative risk as high as 520, and lifetime risk of 13%. 14 Even so, most hamartomas are generally benign.…”
mentioning
confidence: 99%